A lumped parameter and CFD combined approach for the lubrication analysis of a helical gear transmission. Issue 1 (1st December 2022) - Muzzioli, G; Paini, G; Denti, F; Paltrinieri, F; Montorsi, L; Milani, M
Abstract: This paper proposes a combined 1D-3D approach for the lubrication analysis of a standard transmission including two helical gears. A lumped parameter model of the entire lubrication system is developed to predict the flow distribution within the circuit and the localized pressure drops along the lines. This model considers the geometrical features of the real system, and it combines the experimental characteristic curves of the main hydraulic components. The steady-state condition is investigated, and the corresponding lubrication flow is provided as a boundary condition for a three-dimensional CFD model. The overset mesh method is employed to address the instantaneous position of the gears in the contact region and the Volume of Fluid (VOF) model assesses the multi-phase phenomenon. The turbulent behavior of the flow is described by the two-equation realizable k-ε model, and the incompressible assumption is made for both oil and air. The effect of different nozzles configurations on the lubrication efficiency is analyzed and the internal system fluid-dynamics is investigated to point out the oil path. The numerical results are discussed in terms of the volume fraction of oil on the gears teeth, the passive torques at the shafts and the associated power losses under specific operating conditions.